2021
DOI: 10.3389/fpsyg.2021.687165
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Computerized Cognitive Behavioral Therapy on People's Anxiety and Depression During the 6 Months of Wuhan's Lockdown of COVID-19 Epidemic: A Pilot Study

Abstract: Background: The effectiveness of computerized cognitive behavioral therapy (CCBT) has been proven for mild and moderate anxiety and depression. In 2016, the first official Chinese CCBT system was launched by Chinese Cognitive Behavior Therapy Professional Organizations and included four items: getting out of depression, overcoming anxiety, staying away from insomnia and facing Obsessive-compulsive disorder. During the COVID-19 epidemic, Chinese CCBT system served the public for free. This study explored the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
2
4
0
Order By: Relevance
“…The results indicated that 96% of the participants were satisfied with the CBT course and liked cognitive-behavioral training. This result is consistent with those of previous studies,[ 17 18 19 20 ] which showed that CBT can reduce using non-adaptive strategies to control stress in nurses. [ 21 ] Ebert et al .…”
Section: Discussionsupporting
confidence: 93%
“…The results indicated that 96% of the participants were satisfied with the CBT course and liked cognitive-behavioral training. This result is consistent with those of previous studies,[ 17 18 19 20 ] which showed that CBT can reduce using non-adaptive strategies to control stress in nurses. [ 21 ] Ebert et al .…”
Section: Discussionsupporting
confidence: 93%
“…Another aim of this study was to evaluate the effect of CBT on depression in patients with heart failure. The results of our study showed that CBT had a positive effect on reducing depression in patients with heart failure, which was in line with those reported by Lv et al (2021), Liu et al (2021), A‐Tjak et al (2021), and Humphries et al (2021). A review of the literature showed that the effect of this therapeutic intervention on depression in patients with CVDs, especially in those with heart failure, was not well addressed.…”
Section: Discussionsupporting
confidence: 92%
“…Lv et al (2021),Liu et al (2021),A-Tjak et al (2021),and Humphries et al (2021). A review of the literature showed that the effect of this therapeutic intervention on depression in patients with CVDs, especially in those with heart failure, was not well addressed.Therefore, more studies are needed to evaluate the efficacy of this psychotherapy method and the consistency of its effect in reducing depression among patients with heart failure(Gao et al, 2019;Jeyanantham et al, 2017).…”
mentioning
confidence: 99%
“…al [ 29 ] study was not available, we emailed the authors but we did not receive any response; so this article was not included in the present study. In addition, two of the articles including Oehler et al study [ 30 ] due to lack of anxiety scores before and after the intervention and LV et al study [ 31 ] because of presenting insufficient data were excluded from the study. Finally, 11 articles were entered into the study (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the most of the included studies did not clearly stated their methods of randomization and so were placed in unclear risk level in terms of randomization bias, just one study [ 39 ] was low risk in this regard. In none of the studies blinding was performed, however, in just one study [ 31 ], analyzer’s blinding was done. Of other weaknesses of the included studies was their different inclusion criteria, for instance, some of the studies were conducted on people infected with coronavirus, some on people having a history of depression and anxiety, and some on people not infected with coronavirus.…”
Section: Strength and Limitationmentioning
confidence: 99%